Genetic analysis for quantitative traits in Indian bean (Lablab purpureus) - SINGH, PRAMOD KUMAR; RAI, N; LAL, HIRA; SINGH, D V; RAI, K K (The Indian Journal of Agricultural Sciences, 2015)
Genetic study conducted for yield and its traits in Indian bean [Lablab purpureus (L.) Sweet] revealed that heterosis over better parents was found to the extent of 130.78 and 142.27% for green pod yield/plant, 77.22 and 150.52% for number of pods/plant, 16.41 and 37.16% for pod length, 29.70 and 43.41% for pod width, 16.67 and 25.00% for number of seeds/pod, 54.08 and 57.14% for 100-seed weight, 1.46 and 24.56% for seed length, 6.61 and 26.27 % for seed width, 31.40 and 41.10 % for seed thickness, –31.27 and –17.08% for days to first flowering, –30.39 and –14.47% for days to first picking and 5.37 and 10.83 % for fruit set per cluster. The parents KDB 415, VRSEM 923, VRSEM 8 and VRSEM 11 were observed to be good combiners for most of yield contributing characters whereas, the crosses VRSEM 186 × VRSEM 860, VRSEM 11 × VRSEM 894, VRSEM 11 × VRSEM 860, HADB 4 × VRSEM 887 and VRSEM 8 × VRSEM 860 were observed to be most promising combinations for earliness and yield may be advanced for further generation. Most of the yields contributing characters were governed by nonadditive gene action indicating good scope of heterosis breeding in Indian bean for mobilization of yield barrier.